The Effect of Power Distance and Individualism on the Reliability of Audit Evidence - Evinita, Lenny Leorina (8ISC Abstract Proceedings, 2022)
Audit evidence is basic information used by an auditor to provide an opinion on the audited financial statements, and this can be achieved supported by the accuracy of the data provided. This study aims to determine the effect of power distance and individualism on the reliability of audit evidence in public and private Universities in North Sulawesi. This research is quantitative research with a descriptive correlation design, and the population in this study is finance staff at public and private universities. The results indicated power distance and individualism have a significant relationship with the reliability of audit evidence at public/private universities in North Sulawesi. Keywords : Audit evidence, Individualism, Power distance